1992
DOI: 10.1073/pnas.89.7.3159
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of either the E1 or the E2 regulatory gene of human papillomavirus type 16 increases viral immortalization capacity.

Abstract: The "high-risk" human papillomavirus types 16 (HPV-16) and 18 (HPV-18) have been etiologically implicated in the majority of human cervical carcinomas. In these cancers, the viral DNAs are often integrated into the host genome so that expression of the El and the E2 genes is lost, suggesting that disruption of these regulatory genes plays an important role in carcinogenic pgression. Previous studies defiming the viral genes affecting PV-16 transformation functions have used the "prototype" viral genome, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
221
1
8

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(240 citation statements)
references
References 40 publications
10
221
1
8
Order By: Relevance
“…Engineered E2 mutants, particularly of the transactivation region, increase immortalization capacity 28 and transactivation activity. 29 There have, however, been few investigations of the functional significance of natural E2 variants, apart from a study carried out by Veress et al 8 that showed that the transcriptional transactivation potentials of European and AsianAmerican E2 variants were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Engineered E2 mutants, particularly of the transactivation region, increase immortalization capacity 28 and transactivation activity. 29 There have, however, been few investigations of the functional significance of natural E2 variants, apart from a study carried out by Veress et al 8 that showed that the transcriptional transactivation potentials of European and AsianAmerican E2 variants were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Maximal E7 levels correlated with the acquisition of structural chromosomal abnormalities (Alazawi et al, 2002;Pett et al, 2004). High oncogene levels are attributed to the functional loss of the viral E2 gene product which acts as an intrinsic repressor of E6/E7 expression (Romanczuk and Howley, 1992). Moreover, viral-cellular fusion transcripts are devoid of the instability elements located in the 3 0 -region of the viral mRNA and may thus have a longer half-life .…”
Section: Figurementioning
confidence: 99%
“…Integration of the viral DNA into the host genome is frequently observed in invasive cervical carcinomas and in a subset of CIN3 and is thought to be one of the driving factors for progression . In particular the fact, that integration frequently disrupts the viral regulatory gene E2 from its own promoter is taken as an argument for a constitutive strong expression of the viral oncogenes (Baker et al, 1987;Romanczuk and Howley, 1992). Moreover, experimental data suggest that cis-acting elements within the flanking cellular sequences can positively modulate viral gene expression (von Knebel Doeberitz et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Interruption of E2, which normally functions as a transcriptional regulator of E6 and E7, leads to up-regulation of E6 and E7, degradation of p53 and pRB, respectively, and ultimately malignant transformation. [27][28][29] …”
Section: Hpv Pathogenicitymentioning
confidence: 99%